Conceptions analyse of measuring systems in the flexible manufacturing systems - Vasić, Siniša (Journal of Production Engineering, 1991)
Desire for encircling of all activities in manufacturing process by automatization, caused development of manufacturing systems with high integration degree of manufacturing, manipulation, measuring, transportation, storing and control tasks, in other words – FLEXIBLE MANUFACTURING SYSTEMS (PMS). This is changed comprehends about role and tasks of measuring system - from detection tasks to prevention tasks. Besides of this, there is comprehended that if we are wanting to truly automate the factory, that is necessary that the dimensional inspection has the same degree of flexibility and automation as the machine tools used for parts fabrication. Measuring system in EMS ought to involve: - metrological processes relate to dimensional, form and position measurement of workpieces, - metrological processes in correction with detection of tools position and condition, - metrological processes which detect machine tools state and theirs functions. - metrological processes for storing and material flow inspection. In the paper, the conception analyze of measuring systems in flexible manufacturing systems, with stress at workpieces geometrical characteristics measurement is done.